Giant Meningiomas Invading the Cavernous Sinus: The “Inevitable Ones” - Silva, Carlos Eduardo da; Vidaletti, Tamara (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction Giant meningiomas invading the cavernous sinus (GMICSs) are a subgroup of challenging tumors due to their volume and the extent of neurological impairment. Preserving quality of life is one of the most relevant aspects of treating patients with GMICS.Methods A retrospective study was conducted for surgeries performed between 2012 and 2022, including 33 patients presenting meningiomas with the largest diameter of at least 5 cm invading the cavernous sinus. The data from surgical intervention, Simpson grade of resection, tumor location, and morbimortality related to the surgeries were reviewed.Results The group comprised 25 women and 8 men with a median age of 56 years. The mean follow-up period was 52 months. The tumors were in the sphenoid wing, anterior clinoid, spheno-orbital, spheno-petroclival, petroclival, and Meckel's cave. Simpson grade I, II, and III were obtained in 70% of cases. The meningiomas were classified as WHO grade 1 in 94%, grade 2 in 3%, and grade 3 in 3%. The overall mortality was 3%. Permanent cranial nerve deficits occurred in 21%, transient cranial nerve deficits in 42%, cerebrospinal fistula in 15%, and hemiparesis in 18%. The recurrence/regrowth rate was 6%. The Karnofsky Performance Status score of 100 and 90 was 82%.Conclusion The surgical treatment of GMICS is an effective treatment modality with acceptable morbimortality and good long-term control. Involvement of the internal carotid artery is essential to determine the extent of resection inside the cavernous sinus, and training in the microsurgical laboratory is mandatory for safe surgical treatment.
Keywords: meningiomas; cavernous sinus; microsurgery; cranial nerves